The dynamic role of pH in microbial reduction of uranium(VI) in the presence of bicarbonate. (November 2018) - Xie, Jinchuan; Wang, Jinlong; Lin, Jianfeng; Zhou, Xiaohua
Abstract: The negative effect of carbonate on the rate and extent of bioreduction of aqueous U(VI) has been commonly reported. The solution pH is a key chemical factor controlling U(VI)aq species and the Gibbs free energy of reaction. Therefore, it is interesting to study whether the negative effect can be diminished under specific pH conditions. Experiments were conducted using Shewanella putrefaciens under anaerobic conditions with varying pH values (4–9) and bicarbonate concentrations ( [ CO 3 2 − ] T, 0–50 mmol/L). The results showed a clear correlation between the pH-bioreduction edges of U(VI)aq and the [ CO 3 2 − ] T . The specific pH at which the maximum bioreduction occurred (pHmbr ) shifted from slightly basic to acidic pH (∼7.5–∼6.0) as the [ CO 3 2 − ] T increased (2–50 mmol/L). At [ CO 3 2 − ] T = 0, however, no pHmbr was observed in terms of increasing bioreduction with pH (∼100%, pH > 7). In the presence of [ CO 3 2 − ] T, significant bioreduction was observed at pHmbr (∼100% at 2–30 mmol/L [ CO 3 2 − ] T, 93.7% at 50 mmol/L [ CO 3 2 − ] T ), which is in contrast to the previously reported infeasibility of bioreduction at high [ CO 3 2 − ] T . The pH-bioreduction edges were almost comparable to the pH-biosorption edges of U(VI)aq on heat-killed cells, revealing that biosorption is favorable for bioreduction. The end product of U(VI)aq bioreduction was characterized as insoluble nanobiogenic uraninite by HRTEM. The redox potentials of the master complex species of U(VI)aq, such as ( UO 2 ) 4 ( OH ) 7 +, ( UO 2 ) 2 CO 3 ( OH ) 3 −, and UO 2 ( CO 3 ) 3 4 −, were calculated to obtain insights into the thermodynamic reduction mechanism. The observed dynamic role of pH in bioreduction suggests the potential for bioremediation of uranium-contaminated groundwater containing high carbonate concentrations. Graphical abstract: Image 1 Highlights: U(VI)aq bioreduction increased with increasing pH at 0 mM [ CO 3 2 − ] T (∼100%, pH 7 to 9). pHmaximum-bioreduction appeared and shifted from ∼7.5 to ∼6.0 for 2–50 mM [ CO 3 2 − ] T . A clear correlation between pH-bioreduction edges of U(VI)aq and [ CO 3 2 − ] T was observed. The pH-bioreduction edges were almost comparable to the pH-biosorption edges. Shewanella can reduce U(VI)aq at high [ CO 3 2 − ] T (∼100%, 93.7% at 30, 50 mM). [ CO 3 2 − ] T .